2015
DOI: 10.11604/pamj.2015.20.333.4993
|View full text |Cite
|
Sign up to set email alerts
|

Silico-tuberculosis and associated risk factors in central province of Iran

Abstract: IntroductionCo-existence of silicosis and tuberculosis is known as silico-tuberculosis. This article review the frequency of silicosis and tuberculosis in workers who exposed to silica and evaluate influencing factors that may increase the risk of silico-tuberculosis.MethodsAn analytical cross-sectional study was performed in silica exposed workers in central province of Iran during 2011-2012. Sampling method was un-randomized and considering all workers who at least 6 months exposed to silica. The study was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 13 publications
0
23
1
Order By: Relevance
“…For instance, high prevalence levels of drug resistance have been found among HIV patients [11]- [13]. However, other studies have found no association between HIV and drug resistance [9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, high prevalence levels of drug resistance have been found among HIV patients [11]- [13]. However, other studies have found no association between HIV and drug resistance [9].…”
Section: Introductionmentioning
confidence: 99%
“…If exposed to organisms that cause tuberculosis, mycobacterium tuberculosis, silicosis patients will have a risk three times more likely to suffer tuberculosis. 14 The level of silica in the dental laboratory spaces I and II was quite high since materials used in the laboratory contained a lot of silica. Besides that, a range of laboratory processes, such as investing, sandblasting, grinding, polishing and others, can cause silica dust flying in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of a patient with silicosis developing tuberculosis is higher (2.8 to 39 times) than a healthy individual. [9] After extensive literature search, it was noticed that there is lack of studies depicting the exact prevalence of silicosis and other respiratory morbidities among sandstone mine workers in India. With this background, this study was planned to find out the prevalence of silicotuberculosis, silicosis and other respiratory morbidities in sandstone mine workers in Jodhpur district of Rajasthan.…”
Section: Introductionmentioning
confidence: 99%